2019
DOI: 10.1515/rebs-2019-0080
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Investment Drivers in Chinese Economy

Abstract: We examine the predictors of investment in the Chinese economy for the period 1973-2018. Our study adopts the Mark Nerlove (1962) partial adjustment hypothesis combined with instrumental econometric techniques based on the condition of the data used. Our results provide strong evidence that supports savings, export earnings, and final consumption expenditure as correlates of predictors of investment in China. Based on empirical results, we strongly recommend the integration of the unbaked population to a forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Using the ARDL-bound Government domestic debt arrears test for cointegration, Fagbola et al (2020) showed that, in explaining the changes in foreign private investment inflow to Nigeria in both the short run and the long run, the countryspecific factors appear to be more relevant than the global factors. Also, when the drivers of investment in the Chinese economy were examined, there was a strong evidence supporting that earnings from exports, savings and final consumption expenditure are predictors of investment (Shobande and Shodipe, 2019). It is important to note that the effect of government domestic debt arrears on investment by the private sector, by far, has not been investigated directly in the literature.…”
Section: Determinants Of Private Investmentmentioning
confidence: 99%
“…Using the ARDL-bound Government domestic debt arrears test for cointegration, Fagbola et al (2020) showed that, in explaining the changes in foreign private investment inflow to Nigeria in both the short run and the long run, the countryspecific factors appear to be more relevant than the global factors. Also, when the drivers of investment in the Chinese economy were examined, there was a strong evidence supporting that earnings from exports, savings and final consumption expenditure are predictors of investment (Shobande and Shodipe, 2019). It is important to note that the effect of government domestic debt arrears on investment by the private sector, by far, has not been investigated directly in the literature.…”
Section: Determinants Of Private Investmentmentioning
confidence: 99%
“…In order to account for variable omission bias, three control variables are taken on board in the estimation exercises, notably: inflation, taxes on international trade and foreign direct investment (FDI). The choice of these variables is also motivated by contemporary international trade and economic development literature (Cipollina et al, 2016;Fonchamnyo & Akame, 2017;Dary & James, 2018;Blanas & Seric, 2018;Asongu & Kodila-Tedika, 2017;Bahmani-Oskooe & Gelan, 2018;Kaminchia, 2019;Shobande & Shodipe, 2019;Uysal & Mohamoud, 2019). In what follows, their expected signs are discussed.…”
Section: Datamentioning
confidence: 99%
“…The variable proxy's for units of manufacturing that are categorized in relation to the principal mission that entails activities which are done manually (encompassing work in the household), factor-related and poweroriented machinery(United Nations, 1990). Moreover, such an industrialisation indicator has been adopted in recent literature, notably,Kang and Lee (2011), UNIDO(2013), Gui-Diby and Renard, (2015) andShobande and Shodipe (2019).…”
mentioning
confidence: 99%